The effect of economic conditions on accounting conservatism under IFRS in Europe - Antonio Cerqueira; Cláudia Pereira (Review of Economic Perspectives, 2020)
We analyse in detail conservative accounting practices in seventeen European countries, taking into account institutional factors. In addition, we examine the impact of IFRS adoption and the influence of changes in economic conditions on conditional conservatism. Specifically, we study the level of accounting conservatism before and after IFRS adoption detailing for the pre and crisis period and post-crisis period surrounding the 2007/2008 financial crisis. Our findings are consistent with a conservative accounting practice in Europe as a whole and in each country individually. Besides, opposite to that expected, the results provide evidence of more conservative accounting practice in Anglo-Saxon countries, but we find no significant differences in conservatism in Nordic countries. Another finding is a significant decrease in the level of conservatism after IFRS adoption. Regarding the joint impact of IFRS adoption and economic conditions, we find a decrease in conservatism in the pre and crisis period, followed by a substantial increase in the post-crisis period. Our results seem to be in line with the positive accounting theory when suggesting that conservatism plays a fundamental role as corporate governance and efficient contracting mechanism between managers and other stakeholders of the firm. Furthermore, the results suggest that the flexibility provided by IFRS allows adjusting the level of conservatism when economic conditions change.
Keywords: M41; G01; G32; 330; Conditional Conservatism; Economic Conditions; IFRS; Institutional Factors